Assessing impacts of tsetse control in northern Cote d'Ivoire on animal productivity - Rowlands, G.J.; Coulibaly, L.; Hecker, P.; D'Ieteren, G.D.M.; Rarieya, J.M. (OAU/STRC, 1995)
Herd-to-herd variations in the primary biological impact of an intervention can sometimes be utilised to investigate secondary impacts. This approach has been used in the analysis of the effects of tsetse control on calf live weight gain. Nineteen herds of cattle were monitored in the region of Boundiali in northern Cote d'Ivoire from January 1987 to December 1989. From January 1988 to December 1989 insecticide-impregnated biconical traps were used to control tsetse flies in the area. Annual tsets density was reduced by over 95 percent and average monthly trypanosome prevalence in cattle by over 80 percent. Increases in growth rate were plotted against decreases in trypanosome prevalence from 1987 to 1988 and 1989 for each of the 129 herds and regression analysis undertaken with Trypanosoma congolense and T. vivax as independent variables. This analysis showed an increase in growth rate of 3.9 + 1.4 g/d perpercentage unit decrease in overall trypanosome prevalence. When the two species were considered separately this significant increase appeared to be primarily associated with reductions in T. vivax prevalence.